Myelodysplasia as assessed by multiparameter flow cytometry refines prognostic stratification provided by genotypic risk in systemic mastocytosis. Issue 8 (21st May 2019) - Mannelli, Francesco; Gesullo, Francesca; Rotunno, Giada; Pacilli, Annalisa; Bencini, Sara; Annunziato, Francesco; Zanotti, Roberta; Scaffidi, Luigi; Giona, Fiorina; Santopietro, Michelina; Grifoni, Federica; Pieri, Lisa; et al.
Abstract: Systemic mastocytosis (SM) is characterized by extreme heterogeneity of manifestations and prognosis. Several disease‐related biomarkers, including clinical, hematological and molecular variables, have been correlated with prognosis. Although relevant, the mutation profile closely reflects the WHO classification that has per se prognostic value. High‐risk mutations (HRM) are largely confined to advanced forms, and thus fail in providing information regarding progression and outcome in the not‐advanced variants. In this work, we studied hematopoietic cells by multi‐parameter flow cytometry (MFC) in order to highlight dysplastic traits that might provide insights into outcome. A score previously validated for myelodysplastic syndromes, with high reproducibility in standard diagnostics, was used. The application of an MFC score to a cohort of 71 SM cases, concurrently genotyped for configuring a HRM category, resulted in the identification of two separate patients' categories (MFC+ and MFC‐) characterized by significantly different clinical and laboratory features at presentation. The extent of dysplasia by MFC tended to parallel WHO‐category and genotype‐related stratification. MFC+ patients had shorter survival compared to MFC‐ ones, for whom the incidence of progression and/or death was virtually null. Of note, MFC score remained prognostically informative in unadvanced subsets. Furthermore, the integration of MFC and HRM was an independent predictor for outcome, also overcoming WHO‐categories in multivariate analysis for EFS. Our results support the use of MFC analysis in the evaluation of patients with SM, alone and in combination with HRM, for refinement of prognosis assessment.